Learning and Chaining of Motor Primitives for Goal-Directed Locomotion of a Snake-Like Robot with Screw-Drive Units. (14th December 2015) - Chatterjee, Sromona; Nachstedt, Timo; Tamosiunaite, Minija; Wörgötter, Florentin; Enomoto, Yoshihide; Ariizumi, Ryo; Matsuno, Fumitoshi; Manoonpong, Poramate
Motor primitives provide a modular organization to complex behaviours in both vertebrates and invertebrates. Inspired by this, here we generate motor primitives for a complex snake-like robot with screw-drive units, and thence chain and combine them, in order to provide a versatile, goal-directed locomotion for the robot. The behavioural primitives of the robot are generated using a reinforcement learning approach called "Policy Improvement with Path Integrals" (PI 2 ). PI 2 is numerically simple and has the ability to deal with high-dimensional systems. Here, PI 2 is used to learn the robot's motor controls by finding proper locomotion control parameters, like joint angles and screw-drive unit velocities, in a coordinated manner for different goals. Thus, it is able to generate a large repertoire of motor primitives, which are selectively stored to form a primitive library. The learning process was performed using a simulated robot and the learned parameters were successfully transferred to the real robot. By selecting different primitives and properly chaining or combining them, along with parameter interpolation and sensory feedback techniques, the robot can handle tasks like achieving a single goal or multiple goals while avoiding obstacles, and compensating for a change to its body shape.